Cause and correlation in biology : a user's guide to path analysis, structural equations and causal inference - Shipley, Bill, 1960- (Cambridge University Press, 2002)
Written in a jargon-free, conversational style, this book explores the relationship between correlation and causation. It presents a series of statistical methods that can test, and potentially discover, cause-effect relationships between variables in situations in which it is not possible to conduct controlled experiments.